Hollow Bulb Obturator Fabrication Using Glycerin Soap for Management of Hemi Maxillectomy Patient: A Case Report - Reddy, N Simhachalam; Bekkem, Divya; Sreenivasulu, Duggineni (International Journal of Dental Materials, 2025)
The incidence of mucormycosis, particularly rhino-orbital-cerebral involvement, has seen a concerning surge, with many cases necessitating surgical resection followed by prosthetic rehabilitation using obturators. Among various options, the hollow bulb obturator stands out as a practical, economical, and efficient choice for restoring function post-maxillectomy. However, obturators can often become excessively heavy within the defect area, compromising comfort and retention. To address this, hollowing the prosthesis is a well-recognised strategy to reduce weight. This case report outlines a technique for fabricating a closed hollow bulb obturator using a glycerin soap to make it weigh less for an adult patient who underwent maxillectomy. This case report outlines an innovative technique for glycerin soap, which was used to reduce weight, emphasising both functional restoration and prosthetic optimisation.